2017
DOI: 10.16965/ijar.2017.457
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Human Height With Head Length in Indian Individuals

Abstract: Introduction: One of the most important aspects in identifying the personal identity of an individual is stature which is influenced by genetic and environmental factors. Stature exhibits a definite proportional relationship with various parts of the body like head, face, trunk, vertebral column and extremities. Rules of body proportions exhibit consistent ratios among themselves and relative to the total body height and are age, sex and race dependent. They are also of great importance in Fine arts, Anatomy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
3
1
Order By: Relevance
“…The present study with correlation coefficient (r = 0.73) was dissimilar with the study conducted on individuals aged 18–25 years in Ramaiah Medical College, Bengaluru, India 17 in which a weak positive correlation was observed between height and head length (r=0.27). Our study was not in accordance with the study carried out on Bangladeshi Garo adult females 18 with correlation coefficient (r = -0.02) in which head length did not reach statistically significant level with their height.…”
Section: Discussioncontrasting
confidence: 99%
“…The present study with correlation coefficient (r = 0.73) was dissimilar with the study conducted on individuals aged 18–25 years in Ramaiah Medical College, Bengaluru, India 17 in which a weak positive correlation was observed between height and head length (r=0.27). Our study was not in accordance with the study carried out on Bangladeshi Garo adult females 18 with correlation coefficient (r = -0.02) in which head length did not reach statistically significant level with their height.…”
Section: Discussioncontrasting
confidence: 99%
“…A study conducted in 2013 showed that the mean and standard deviation values of the parameters were as follows: cranial height 130.68 ± 7.77 mm The maximum cranial width and the maximum cranial length results obtained in our study are similar to the literature data but Khan et al and Shankar et al showed that the values were found to be higher than our results. [10][11][12][13][14][15][16][17] These results are shown that Table 3. Upper face height values in the literature were found to be low compared to the results in our study.…”
Section: Discussionmentioning
confidence: 82%
“…Much less is known about the extent of the association between CF and BC, although the existing data leaves room for little doubt that such an association exists. For example, the correlation between head circumference and various body trunk measurements, as well as body height and head length are well known and repeatedly reported (Roosenboom et al, 2016;Shankar et al, 2017). In this regard, it is important to mention that not only does CF morphology correlate with body size, but somatic growth was found to be a significant determinant of CF morphology (Larson et al, 2018).…”
mentioning
confidence: 89%